Perancangan Aplikasi Container Loading Problem dengan Menggunakan Maximal Space Algorithm - Rosalinda Rosalinda; Lely Hiryanto; Gunadi Gan (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
This paper presentmaximalspace algorithmtosolve the problem ofloadingcargointo containers.This algorithmis presentedin two phases, that isconstructive phasesandimprovementphases. With constructivephase, optimal resultsareobtainedin the use ofphaseimprovement.The result of this experiment is the objection objective of this application has been achieved. It’s because the data testing can load cargo to container successfully. However, the size of each cargo can affect the rest of the container volume.